(untitled) - Kemper, John D. (New York, 2001)
Thoroughly updated to reflect modern engineering practice, the fifth edition of Engineers and Their Profession offers in-depth coverage of the engineering enterprise and engineers' involvement in key areas of American endeavor. Comprehensive and accessible, it is an ideal text for an upper-level undergraduate course in engineering professionalism. It is also suitable for introductory freshman engineering courses and for high school and college students considering a career in this diverse field. The book provides a broad overview of the profession and helps students make the transition from college to industry by describing the reality of the business world that they will soon enter. This revised edition includes up-to-date and extensive coverage of ethics and personal responsibility, making it especially useful for engineering professionals. The text is enhanced by study questions at the end of each chapter and numerous figures and tables throughout.
Keywords: Engineering